Pan-urologic cancer genomic subtypes that transcend tissue of origin - Fengju Chen (Nature Portfolio, 2017)
Urological cancers have disparate tissues and cells of origin but share many molecular features. Here, the authors use multidimensional and comprehensive molecular characterization to classify urological cancers into nine major genomic subtypes, highlighting potential therapeutic targets.